(untitled) (Journal of Geography and Environmental Management, 2019)
Considering the river valley as fl uvial geomorphological system, M. Zh. Zhandaev developed a series of new questions about the formation of river valleys in mountain countries. These include theoretical aspects of initial and fi nal stages of the formation of river valleys, meandering channels of the processes of mountain rivers, river interceptions. Justifi ed by the provisions of the transgressive erosion and the relative stability of the watershed. The process of meandering is one of the main channel fl ow patterns.